Analysis of the Stability of Stored Adenosine 5′-monophosphate used for Bronchoprovocation - Martı́nez-Garcı́a, Miguel Angel; Perpiñá-Tordera, Miguel; Vila, Virtudes; Compte-Torrero, Luis; De Diego-Damiá, Alfredo; Macián-Gisbert, Vicente (Pulmonary Pharmacology & Therapeutics, 2002)
Adenosine 5′-monophosphate (AMP) bronchial challenge has been shown to be very useful tool in the diagnosis of asthma. Freshly test solutions are prepared just prior to each test in most of the studies. The objective of this study was to assess the stability of AMP solutions at different temperatures using a reversed-phase high-performance liquid chromatography assay. Sodium salt AMP solutions in concentrations of 0.03mg/ml and 400mg/ml were analyzed. One aliquot was kept at room temperature (20–25°C) and the others were refrigerated at 4°C. Room temperature stored samples were analyzed daily. Refrigerated stored samples were analyzed daily for first 15 days and then weekly. The duration of the study was 25 weeks. Samples were injected into the chromatograph column in quadruplicate and quantification was based on the arithmetic mean and standard deviation (±SD) of four measurements. Room temperature stored samples at concentrations of 0.03mg/ml showed a mean percent variation greater than 10% at day 9 and greater than 75% at day 14. Samples at concentrations of 400mg/ml maintained almost the initial concentration during the first 10 days, but decomposition occurred thereafter. In contrast, there was no significant degradation of refrigerated stored samples throughout the study period. We conclude the exposure to room temperature of AMP solutions results in a substantial loss of the initial concentration, but the shelf life of adequately prepared stock AMP solutions stored at 4°C is at least 25 weeks.